Exploring the Relationship Between Ejection Fraction, Arterial Stiffness, NT-proBNP, and Hospitalization Risk in Heart Failure Patients - Gyongyi Osser; Brigitte Osser; Csongor Toth; Caius Calin Miuța; Gabriel Roberto Marconi; Laura Ioana Bondar (Diagnostics)
Background/Objectives: Heart failure (HF) remains a leading cause of hospitalization and morbidity. Arterial stiffness, measured by pulse wave velocity (PWV) and the augmentation index (AIx), has been linked to HF severity and prognosis. This study investigates the relationship between clinical parameters, biochemical indicators, and arterial stiffness in hospitalized patients with HF, aiming to identify predictors of hospitalization and improve patient management. Methods: This cross-sectional study included 98 patients admitted with HF: 53 with acutely decompensated HF (sudden worsening of symptoms) and 45 with chronic HF (stable symptoms of HF). Clinical and biochemical parameters, including ejection fraction (EF), N-terminal prohormone of brain natriuretic peptide (NT-proBNP) levels, and arterial stiffness indicators (PWV and AIx), were measured at admission. During follow-up, 59 patients required re-hospitalization due to acutely decompensated HF, while 39 remained outpatients without further hospitalization. The relationship between these parameters was analyzed using Pearson correlation coefficients, and multiple Cox regression analysis was conducted to identify independent predictors of re-hospitalization. Results: A significant negative correlation between EF and PWV was found (r = −0.853, 95% CI [−0.910, −0.764]), suggesting an association between improved heart function (higher EF) and reduced arterial stiffness (lower PWV). A moderate positive correlation between EF and AIx (r = 0.626, 95% CI [0.473, 0.805]) suggests that, while higher EF is associated with increased AIx, the relationship is weaker compared to EF and PWV. This may reflect differing contributions of vascular and myocardial factors to HF severity. Hospitalized patients exhibited significantly poorer clinical and biochemical profiles, including higher NT-proBNP levels (p < 0.001) and worse blood pressure (BP) measurements (systolic and diastolic, p < 0.01). Multiple Cox regression analysis identified PWV, Aix, and NT-proBNP as independent predictors of re-hospitalization in HF patients, with significant hazard ratios: PWV (HR = 1.15, p = 0.02), AIx (HR = 1.03, p = 0.02), and NT-proBNP (HR = 1.0001, p < 0.01). Conclusions: Arterial stiffness indices (PWV and AIx), EF, and NT-proBNP were identified as significant predictors of re-hospitalization in HF patients. These findings suggest that integrating arterial stiffness measurements into routine clinical assessments may enhance the risk stratification and inform targeted interventions to reduce hospitalizations and improve outcomes.